2017
DOI: 10.1177/1539449217708554
|View full text |Cite
|
Sign up to set email alerts
|

Driving Errors That Predict On-Road Outcomes in Adults With Multiple Sclerosis

Abstract: Driving errors that predict on-road outcomes for persons with multiple sclerosis (PwMS) are not well studied. The objective of this study was to determine whether adjustment-to-stimuli and gap acceptance errors significantly predict passing/failing a standardized on-road assessment of PwMS. Thirty-seven participants completed visual ability and visual attention assessments, and participated in an on-road assessment, where seven types of driving errors and pass/fail outcomes were determined. Adjustment-to-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(42 citation statements)
references
References 25 publications
4
38
0
Order By: Relevance
“…In the literature, twelve studies document findings of clinical and on-road assessments for drivers with MS Krasniuk et al, 2017;. These study findings are summarized in Appendix A (p. 153-157).…”
Section: Clinical Testsmentioning
confidence: 99%
“…In the literature, twelve studies document findings of clinical and on-road assessments for drivers with MS Krasniuk et al, 2017;. These study findings are summarized in Appendix A (p. 153-157).…”
Section: Clinical Testsmentioning
confidence: 99%
“…Other characteristics of pwMS have also been related to the fitness to drive. These studies revealed that males with MS more often pass a driving test than females (Lincoln and Radford, 2008) and that lower education was associated with a greater chance of failing a driving test or failing such a test with more violations (Krasniuk et al, 2017;Devos et al, 2017). Furthermore, in one study it was observed that education was positively associated with driving related attention (Shawaryn et al, 2002).…”
Section: Fitness To Drivementioning
confidence: 97%
“…Six studies assessing fitness to drive of pwMS by means of an onroad driving test showed pass rates of 78%-84% (Classen et al, 2018;Akinwuntan et al, 2014;Krasniuk et al, 2017;Morrow et al, 2018;Akinwuntan et al, 2018). However, one study (Ranchet et al, 2015) found a pass rate of 94%, while another study similar in design found a lower pass rate of 62% (Lincoln and Radford, 2008).…”
Section: Fitness To Drivementioning
confidence: 99%
See 2 more Smart Citations